The Deaths of Louis XVI: Regicide and the French Political Imagination - Dunn, Susan (Literature in History Ser., 1994)
Cover Page -- Half-title Page -- Title Page -- Copyright Page -- Dedication age -- Contents -- Foreword -- Acknowledgments -- Introduction -- Part I: Political Myths -- Chapter One: Louis XVI and the Cult of Human Sacrifice -- Chapter Two: Louis XVI and Joan of Arc -- Chapter Three: Michclet and Lamartine: Regicide, Passion, and Compassion -- Part II: Earth: Literary Myths -- Chapter Four: Louis XVI and His Executioners -- Chapter Five: Victor Hugo, Kingship, and Louis XVI -- Chapter Six: Camus and Louis XVI: A Modern Elegy for the Martyred King -- Conclusion -- Index.